Forecast-informed reservoir operations to guide hydropower and agriculture allocations in the Blue Nile basin, Ethiopia. Issue 2 (4th March 2021) - Alexander, Sarah; Yang, Guang; Addisu, Girmachew; Block, Paul
ABSTRACT: Predictive hydroclimate information, coupled with reservoir system models, offers the potential to mitigate climate variability risks. Prior methodologies rely on sub-seasonal, dynamic/synthetic forecasts at short timescales, which challenge application in practice. Here, coupling a local-scale seasonal, statistical streamflow forecast with a reservoir model addresses this gap, to explore hydropower and agricultural production benefits under various operational strategies. Forecast-informed optimization of reservoir releases increases energy production (6–14%), agriculture allocations (54–68%), and net profit. Application to Ethiopia showcases a novel seasonal-scale statistical forecast coupled reservoir model that translates hydroclimatic predictions into actionable information for better management at the local scale.